Multimodality Imaging of Somatostatin Receptor–Positive Tumors with Nuclear and Bioluminescence Imaging - Stefan E. Pool; Timo L.M. ten Hagen; Stuart Koelewijn; Marion de Jong; Gerben A. Koning (Molecular Imaging)
Multimodal bioluminescence (BLI) and single-photon emission computed tomography/computed tomography (SPECT/CT) imaging were investigated as means to monitor somatostatin receptor subtype 2 (SST 2 )-positive neuroendocrine tumors as both a subcutaneously implanted and a liver metastasis animal model in mice and rats. Ultimately, such a model will be of use for studying SST 2 -targeted peptide receptor radionuclide therapy (PRRT). CA20948 cells were transfected with a green fluorescent protein/luciferase plasmid construct. Cells were inoculated subcutaneously in the shoulder of nude mice: nontransfected cells in the left shoulder and transfected cells in the right shoulder. BLI, SPECT/CT imaging, biodistribution analysis, and ex vivo autoradiography of the tumors were performed. BLI and SPECT/CT imaging were also performed on an intrahepatic tumor model in the rat. Caliper volume measurement of transfected tumors could be correlated with BLI measurements ( 2 = .76). SPECT/CT imaging showed high levels of accumulation of 111 In-DTPA-octreotide in control and transfected tumors, which was confirmed by biodistribution analysis and autoradiography. Subcapsular inoculation of transfected cells in rat liver resulted in an intrahepatic tumor, which could be visualized by both SPECT/CT and BLI. Transfection of CA20948 tumor cells did not alter the growth properties of the cell line or the expression of SST 2 . Transfected tumors could be clearly visualized by BLI and SPECT/CT imaging. The transfected SST 2 -positive tumor cell line could represent a novel preclinical model for tumor monitoring in studies that aim at further optimizing PRRT for neuroendocrine tumors.